Toxic work environment (Entrepreneurship Journal for Finance and Business, 2026)
The work environment and its components have gained great importance today due to the impact it has on its human capital. In recent years, studies have increased that discussed the negative and positive role of the work environment, as it is considered the main nerve of the organization’s success or failure. Here, we tried to shed light on some of the issues that can hinder the work of organizations and obstruct the achievement of their goals, including a toxic environment that makes employees feel the presence of penalties, the possibility of rejection, and being held guilty, with the necessity of constant defensiveness and humiliation. This is evident through the organizational leadership responsible for the organization, the culture of this organization and its employees, weak communication between them or dispersion, and the presence of blocs that cause fatigue and the impact they leave and the threat they pose if the matter is not addressed. This leads to a decrease in employee performance productivity, job attrition, an increase in work turnover, lack of progress at work, an inability to commit and achieve a balance between work and life, the occurrence of excessive professional fatigue, and conflicts that cause confusion in understanding roles. These are all signs that confirm the existence of a toxic work environment. Therefore, organizations whose environment is described as toxic face difficulty in maintaining, supporting, and attracting experienced human capital. One of the most important recommendations here is the necessity of encouraging and highlighting Positives and good relationships at work that serve the public interest and create a supportive social network that supports these relationships, while not forgetting to set red lines that should not be crossed and to maintain a safe distance with colleagues.